Choice of Pole and Ski Lengths Among Elite Cross-Country Skiers: The Influence of Sex and Performance Level - Torvik, Per-Øyvind; van den Tillaar, Roland; Sandbakk, Øyvind (Frontiers in sports and active living, 2021)
Cross-country (XC) skiers employ whole-body exercise to generate speed through poles and skis. The choice of optimal pole and ski lengths are therefore of high importance. The aim of this study was to document pole and ski lengths among elite male and female cross-country skiers in the classical and skating styles and to investigate sex differences in body-height-normalized pole and ski lengths. Our secondary purpose was to correlate body-height-normalized pole and ski lengths with performance level within both sexes. In total, Norwegian men and women ( n = 87 and 36, respectively), participating in the Norwegian XC championship 2020, were investigated. Most athletes used poles close to the length allowed by the International Ski Federation (FIS) in the classical style among both sexes, with men using slightly longer poles than women ( p < 0.05). Body-height-normalized pole lengths in skating were similar in men and women (around 90% of body height). Women used relatively longer ski lengths than men in both styles ( p < 0.05). Women showed moderate correlations ( r = 0.43, p < 0.05) between body-height-normalized pole lengths and sprint performance. Male and female cross-country skiers use as long classical ski poles as possible within the current regulations, while they use skating poles similar to recommendations given by the industry. The fact that men use longer body-height-normalized poles than women, where there is a correlation between pole length and sprint performance, indicate that faster women are able to better utilize the potential of using longer poles when double-poling. However, while women use relatively longer skis than men, no correlation with performance occurred for any of the sexes.